Splenic undifferentiated high grade pleomorphic sarcoma of a small size with fatal tumor rupture - Amatya, BM; Sawabe, M; Arai, T; Kumakawa, T; Takubo, K; Kimula, Y; Koike, M (Journal of Pathology of Nepal, 2011)
(The order of authors on this article was changed on 09/01/2012.) Primary undifferentiated pleomorphic sarcoma of the spleen is a rare and highly aggressive neoplasm that usually presents with splenomegaly, constitutional symptoms and frequent distant metastases. We report a case of 77-year old male patient with a past history of dissecting aortic aneurysm that developed acute hemorrhagic shock. Aneurysmal rupture was clinically suspected, but the postmortem examination revealed a 25 mm-sized tumor in an atrophic spleen weighing 65 gram with massive retroperitoneal bleeding. Metastases were found in the right renal hilus, the right adrenal gland and femoral bone marrow. Histology of the tumor showed undifferentiated pleomorphic sarcoma. Tumor rupture with fatal bleeding and systemic metastases had occurred despite the small size of the tumor. Tumor size is not a reliable predictor of systemic metastasis or tumor rupture for splenic undifferentiated pleomorphic sarcoma. Keywords: Undifferentiated pleomorphic sarcoma; Malignant fibrous histiocytoma; Splenic neoplasms; Retroperitoneal hemorrhage DOI: http://dx.doi.org/10.3126/jpn.v1i2.5411 JPN 2011; 1(2): 151-153